2019
DOI: 10.3168/jds.2019-16392
|View full text |Cite
|
Sign up to set email alerts
|

Typing and evaluating heat resistance of Bacillus cereus sensu stricto isolated from the processing environment of powdered infant formula

Abstract: Bacillus cereus sensu lato is one of the most harmful bacterial groups affecting the quality and safety of powdered infant formula (PIF). In this study, samples were collected from the raw materials and processing environments of PIF. A total of 84 isolates were identified as Bacillus cereus sensu stricto (B. cereus s. s.) by 16S rRNA analysis, molecular typing technology, and physiological and biochemical tests. The 84 B. cereus s. s. strains were assigned to panC group II, group III, and group IV. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…It has also been observed that spores from mesophilic strains survive food processing and heat treatment better than spores from psychrotrophic strains [150]. When the seven major phylogenetic groups within the B. cereus group according to Guinebretiére et al [151] were investigated, a high thermal resistance was found for group III (mesophilic) and a comparatively low resistance for psychrotolerant group VI [152][153][154]. Furthermore, a positive correlation between spore heat resistance and growth temperatures of the strains was observed [153].…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 96%
“…It has also been observed that spores from mesophilic strains survive food processing and heat treatment better than spores from psychrotrophic strains [150]. When the seven major phylogenetic groups within the B. cereus group according to Guinebretiére et al [151] were investigated, a high thermal resistance was found for group III (mesophilic) and a comparatively low resistance for psychrotolerant group VI [152][153][154]. Furthermore, a positive correlation between spore heat resistance and growth temperatures of the strains was observed [153].…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 96%
“…Concerning infant formula in the Chinese market, two reports were produced in 2012–2013 and 2015, according to which 14% and 42% of formula contained B. cereus , respectively. It was also revealed that 8.2% of PIF samples in China were contaminated with B. cereus strains [ 78 ]. Overall, the regional characteristics of the prevalence of B. cereus in dairy products in China cannot be clearly defined by latitudes or longitudes.…”
Section: Prevalence Of Bacillus Cereus From Daimentioning
confidence: 99%
“…For example, the following names have been used to refer to ces-negative, group III strains: emetic-like B. cereus, B. cereus, group III B. cereus, B. paranthracis, or B. cereus sensu stricto/B. cereus s.s, although it should be noted that B. cereus sensu stricto is a misnomer; as mentioned previously, group III strains do not fall within the genomospecies boundary of the B. cereus sensu stricto type strain and thus are not actually members of the B. cereus sensu stricto species (12,16,26,(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 90%